2012
DOI: 10.1371/journal.pntd.0001456
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Schistosoma japonicum Egg-Induced Liver Fibrosis by Natural Killer Cells

Abstract: The role of natural killer (NK) cells in infection-induced liver fibrosis remains obscure. In this study, we elucidated the effect of NK cells on Schistosoma japonicum (S. japonicum) egg-induced liver fibrosis. Liver fibrosis was induced by infecting C57BL/6 mice with 18–20 cercariae of S. japonicum. Anti-ASGM1 antibody was used to deplete NK cells. Toll-like receptor 3 ligand, polyinosinic-polycytidylic acid (poly I∶C) was used to enhance the activation of NK cells. Results showed that NK cells were accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…NK cell killing of activated HSCs was first demonstrated by two different groups using mouse models in 2006, which play an important role in inhibiting liver fibrosis; 8, 9 these results were later confirmed in other mouse models of liver fibrosis. 7, 65, 66 The important antifibrotic functions of NK cells were also recently demonstrated in HCV patients by several clinical studies. 5‐7 First, in vitro coculture of activated primary human HSCs with human NK cells resulted in the killing of the HSCs by the production of TRAIL and FasL.…”
Section: Nk Cells and Human Liver Diseasesmentioning
confidence: 89%
“…NK cell killing of activated HSCs was first demonstrated by two different groups using mouse models in 2006, which play an important role in inhibiting liver fibrosis; 8, 9 these results were later confirmed in other mouse models of liver fibrosis. 7, 65, 66 The important antifibrotic functions of NK cells were also recently demonstrated in HCV patients by several clinical studies. 5‐7 First, in vitro coculture of activated primary human HSCs with human NK cells resulted in the killing of the HSCs by the production of TRAIL and FasL.…”
Section: Nk Cells and Human Liver Diseasesmentioning
confidence: 89%
“…In chronic schistosomiasis, a downregulation of the immune reaction can be observed (66). B cells (67) and a pathway dependent on the stimulation of the IL-13 receptor α2 (68) as well as activated IFN-γ-producing NK cells (69) have been suggested as being responsible for this downregulation. Finally, HSCs stimulated by cytokines, including TGF-β1 produced by Th2 cells responding to schistosome antigens, transdifferentiate into myofibroblasts, producing excessive amounts of type III, VI, and I collagen (63,70).…”
Section: Infection and Fibrosismentioning
confidence: 99%
“…Particularly, natural killer (NK) cells, being abundant in the liver and serving as the major innate immune component against infection and tumours10, also play an important role in inhibiting liver fibrosis1112. These results were later confirmed in other mouse models of liver fibrosis131415 and in HCV patients by several clinical studies141617. Taken together, these studies suggested that the host could orchestrate highly complex immune responses to regulate liver fibrogenesis during chronic virus infection.…”
mentioning
confidence: 91%